AN EXPLORATORY STUDY OF THE IMPACT OF ARTIFICIAL INTELLIGENCE ON THE JUDICIARY PRODUCTIVITY AND EFFICIENCY - Ribeiro, Max Ricardo Borges; Carneiro, Glauco de Figueiredo (ARACÊ, 2025)
This exploratory study investigates the application of artificial intelligence (AI) within the Sergipe State Court, focusing on its impact on efficiency, productivity, and user satisfaction. AI technologies, such as machine learning algorithms and natural language processing (NLP), have streamlined judicial processes, including automated case prioritization, enhanced legal research, and predictive analytics for informed decision-making. The study highlights AI’s potential to ensure consistent and fair judgments, increasing satisfaction among judicial service users in Sergipe. However, it also addresses significant risks, including algorithmic biases and concerns about AI’s trustworthiness and transparency. These risks emphasize the need for careful oversight and monitoring to prevent adverse impacts on justice. According to the exploratory research, the main benefit expected by users is the significant increase in efficiency and productivity, however, the main identified risk lies in concerns about algorithmic biases and trust in AI systems, a factor considered essential or very relevant by a significant portion of respondents. Regarding the services to be prioritized for enhancement with AI, the grouping of documents by similarity emerges as primordial, considered essential or very relevant by most employees. The study concludes with recommendations for integrating AI to improve operational efficiency and the credibility of the Sergipe State Court.